2018
DOI: 10.1038/s41467-018-05843-9
|View full text |Cite
|
Sign up to set email alerts
|

Cas9 immunity creates challenges for CRISPR gene editing therapies

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 is a genome-editing technology1,2 that utilizes archaeal and bacterial Cas9 nucleases to introduce double-stranded breaks in DNA at targeted sites. These breaks can be used to remove, replace, or add pieces of DNA. While not the first genome editor, CRISPR-Cas9 is efficient and cost-effective because cutting is guided by a strand of RNA rather than a protein. The potential uses in health care are plentiful, from disrupting dominant genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(137 citation statements)
references
References 15 publications
1
121
0
2
Order By: Relevance
“…126,127 The barriers to broad clinical translation of CRISPR-Cas systems include (1) imperfect DNA-targeting specificity leading to off-target effects, 128 (2) low efficiency of genome editing using HDR, 129 and (3) challenging delivery of CRISPR-Cas components. 130 More recently, concerns were raised about the immune response toward Cas9 and the presence of neutralizing antibodies; 131 the potential for large deletions and complex rearrangement induced by Cas9 cleavage; 132 and activation of the p53 pathway, which can antagonize the efficiency of Cas9-mediated gene editing. 133 The therapeutic protein itself can also be a source of immune response, in particular when treating genetic diseases.…”
Section: Biodegradability and Targeting Issues With Non-viral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…126,127 The barriers to broad clinical translation of CRISPR-Cas systems include (1) imperfect DNA-targeting specificity leading to off-target effects, 128 (2) low efficiency of genome editing using HDR, 129 and (3) challenging delivery of CRISPR-Cas components. 130 More recently, concerns were raised about the immune response toward Cas9 and the presence of neutralizing antibodies; 131 the potential for large deletions and complex rearrangement induced by Cas9 cleavage; 132 and activation of the p53 pathway, which can antagonize the efficiency of Cas9-mediated gene editing. 133 The therapeutic protein itself can also be a source of immune response, in particular when treating genetic diseases.…”
Section: Biodegradability and Targeting Issues With Non-viral Vectorsmentioning
confidence: 99%
“…In addition, the transient nature of the mRNA expression limits the presence of the nuclease inside the cells, reducing the risks of off-target cutting and immune response toward Cas9 protein; however, the intracellular presence of Cas9 protein has been more persistent after mRNA expression as compared to the delivery of Cas9-RNPs. 131 Thus far several studies have demonstrated the therapeutic potential of local in vivo Cas9-RNP delivery, 136,137 while systemic RNP delivery still needs to be evaluated in contrast to more established mRNA-based approaches. 130 The use of mRNA could also mitigate obstacles associated with Cas9-RNPs, such as manufacturing and preserving the activity of Cas9 protein as well as challenging in vivo protein delivery.…”
Section: Biodegradability and Targeting Issues With Non-viral Vectorsmentioning
confidence: 99%
“…However, unexpected nuances of the CRISPR-Cas9 editing system continue to emerge. Varied biological responses to CRISPR-Cas9, such as DNA damage repair (Haapaniemi et al, 2018), enzymatic immunity (Crudele and Chamberlain, 2018), and alternative templating (Ma et al, 2017) exemplify our still nascent understanding of DNA and RNA editing. Furthermore, natural human genetic variation has been shown to influence both the efficaciousness of on-target editing and the frequency of off-target editing (Lessard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have highlighted pre-existing immunity towards both SpCas9 and SaCas9 in the human population, with a high prevalence of both Cas9-reactive T cells and antibodies [71]. Although it is still unclear whether adeno-associated virus delivery of Cas9 leads to the immune rejection of transduced cells in vivo , strategies to control the anti-Cas9 T cell responses, such as transient immunosuppression or engineering Cas9 proteins with mutated T cell epitopes, are being considered [72]. Another limitation of Cas9 for its use in gene therapy resides in its rather large size, which is incompatible for efficient packaging into adeno-associated virus vectors, the most commonly used delivery systems in gene therapy.…”
Section: Future Perspectivementioning
confidence: 99%